Local buckling behaviour of wire arc additively manufactured stainless steel I-shaped and cruciform section stub columns - Xinya Huang; Ziyi Wang; Man-Tai Chen; Yating Liang; Ou Zhao (Engineering Structures, 2026)

Large-scale crop dataset and deep learning-based multi-modal fusion framework for more accurate G × E genomic prediction - Qixiang Zou; Shuaishuai Tai; Qianguang Yuan; Yating Nie; Heping Gou; Longfei Wang; Chuanxiu Li; Yi Jing; Fangchun Dong; Zhen Yue; Yi Rong; Xiaodong Fang; et al. (Computers and Electronics in Agriculture, 2025)

A stable delivery system for curcumin: Fabrication and characterization of self-assembling acylated kidney bean protein isolate nanogels - Zhihui Yu; Yating Gao; Ziqi Shang; Tengfei Wang; Xuli He; Jian Lei; Fei Tai; Lixin Zhang; Yisheng Chen (Food Chemistry, 2024)

Investigating the Ice-Induced Fatigue Damage of Offshore Structures by Field Observations - Yating Huang; Songsong Yu; Tai An; Guojun Wang; Dayong Zhang (Journal of Marine Science and Engineering, 2023)
The oil and natural gas resources of the Bohai Sea are mainly marginal oil fields, and there are currently a large number of structures that are approaching or have reached the end of their service life called aging structures. The interactions between ice and offshore structures could lead to significant ice-induced vibration. Ice-induced vibrations may evoke fatigue damage in tubular joints, which results in severe dangers for offshore platforms in the Bohai Sea. Dynamic ice force models and sea ice fatigue environmental parameters have not been well developed in the current design codes. It is not accurate to evaluate the fatigue damage of structures only with numerical simulation. In this paper, a faster method for evaluating fatigue damage on aging structures is proposed. Firstly, the approximate linear relationship between the fatigue hot spot stress and the vibration response of the deck structure has been discovered using dynamic analysis for jacket platform of Bohai Sea. Then, the procedure of the fatigue damage evaluation of the aging structures in the Bohai Sea is established. Finally, the numerical simulation of the structure is carried out considering ice thickness, ice velocity, ice direction, and action height of sea ice. Fatigue damage is calculated by the fatigue hot spot stress and the Palmgren–Miner rule. The measured data on the platform in the Bohai Sea are selected to obtain the fatigue hot spot stress using a mathematical model. The fatigue damage results considering the actual ice conditions of a jacket structure in the Bohai Sea are compared using the proposed method and finite element analysis. The comparison of the results verifies the rationality of the method proposed in this work.

Promoting photocatalytic performance of TiO2 nanomaterials by structural and electronic modulation - Han Cao; Fangyuan Liu; Yating Tai; Wei Wang; Xiaoyu Li; Pengyao Li; Hongzuo Zhao; Yongqing Xia; Shengjie Wang (Chemical Engineering Journal, 2023)

Sociality and oxytocin and vasopressin in the brain of male and female dominant and subordinate mandarin voles - Xufeng Qiao; Yating Yan; Ruiyong Wu; Fadao Tai; Ping Hao; Yan Cao; Jianli Wang (Journal of Comparative Physiology A, 2014)